ASSESSMENT OF RISK FACTORS OF PREMATURE BIRTH - A.E. SHKLYAEV; M.V. SEMYONOVA; A.S. LYALINA; I.E. MAKSIMOV (Avicenna Tajik State Medical University, 2019)
Objective: Assessment of the significance of possible etiological factors in the development of early-premature birth in the Udmurt Republic. Methods: The main monitoring group consisted of 94 women with extremely early premature birth, the comparison group - 94 women with spontaneous childbirth in time. The estimation of the significance of risk factors was carried out by means of determination of relative risk value (RR), which characterizes the relationship between exposure and pathology. The data obtained as a result of the research are processed by generally accepted methods of variation statistics. Results: The obtained data on the significant influence of the morphofunctional state of the placenta (chronic placental insufficiency, relative risk, RR=3.4), premature rupture of the fetal membranes (RR=3.9), cervical insufficiency (RR=23) for the development of early premature childbirth. The somatic history of women with extremely early premature birth is a pathology of the cardiovascular system (arterial hypertension, RR=5.7), liver and biliary tract (dyskinesia, RR=3.7), iron deficiency anemia (RR=5.0), what is important for the adequate development and functioning of the placenta. Conclusion: Premature birth still remains an important problem in obstetrics, neonatology, and pediatrics. Of the risk factors we have identified for the Udmurt Republic, the most important consider the cervical insufficiency, premature birth in the anamnesis, inflammatory processes of the cervix, etc. Pregravid preparation taking into account these risk factors, and also the correction of extragenital pathology, can help to reduce the incidence of early premature birth.